Analysis on clinical features and outcome of elderly patients with peritoneal dialysis - ZHAO Li-juan; SUN Shi-ren; ZHOU Mei-lan; YANG Jun; XU Guo-shuang (Linchuang shenzangbing zazhi)
Objective To explore the clinical features of elderly patients undergoing peritoneal dialysis and the related factors influencing their survival rate. Methods A retrospective study design was adopted, and those patients with peritoneal dialysis at the age ≥65, treated in Xijing Hospital, the Air Force Medical University from Jan. 2012 to Jun. 2018, were enrolled. Their clinical data were analyzed, including the related clinical data and laboratory data before dialysis and during the follow-up; and the data on infection and prognosis associated with peritoneal dialysis were recorded. Overall and technical survival rates, and their influencing factors were analyzed further. Results Seventy-eight patients with peritoneal dialysis during the study period were enrolled, including 35 cases of primary glomerular diseases(44.9%), 34 ones of diabetic nephropathy(43.6%), 6 ones of hypertensive renal injury(7.7%), and 3 other ones(3.8%). During the follow-up, 43 patients withdrew, of which 39 patients died. The death events included 19 cases of cardiovascular events(48.7%), and 6 cases of peritonitis associated with peritoneal dialysis(15.4%). The median survival time of elder patients with peritoneal dialysis was 42(30.1, 53.8) months and the median technical survival time 37(30.8, 43.2) months. The five-year survival rates were 86.8%, 70.5%, 53.9%, 41.8% and 32.5% at 1, 2, 3, 4 and 5 years after peritoneal dialysis initiation, respectively. The technical survival rates were 85.5%, 67.9%, 51.9%, 35.1% and 27.3% at 1, 2, 3, 4 and 5 years, respectively. Comparison between the survival group and the death group showed statistically significant differences in dialysis adequacy, diabetes, serum albumin, potassium, calcium levels and platelets after dialysis(P<0.05). Multivariate analysis showed that hypoalbuminemia and insufficient dialysis were independent factors of mortality in elder patients with peritoneal dialysis. Conclusions Mortality was higher in elderly patients. Factors affecting mortality in elderly patients included dialysis insufficient and the albumin levels after dialysis.